إدارة جودة التعليم اللغة العربية في المدرسة - Mokoginta, Siti Mustika Vevi; Hadawiyah, Rabiatul; Syamsudin, Ahmad; Hilmi, Danial (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
Abstract: This study aims to determine how the quality management of Arabic learning in schools in Indonesia. This study uses a descriptive qualitative approach using case study research methods. Data collection was done by interview and documentation. The results of this study indicate that quality management in Arabic learning in schools is found to a) Arabic language learning in schools becomes more appropriate, by building interactive, inspiring, fun and motivating learning. b) Arabic language learning in schools is getting better, so that it is able to meet student graduation standards, by building learning support facilities such as language labs and language environments. This study also reveals that there are factors that support the success of learning Arabic, namely internal and external factors, such as the language environment, self-motivation, professional teachers and adequate learning facilities. Keywords: Management, Quality, Arabic Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana manajemen mutu pembelajaran bahasa Arab di sekolah. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan menggunakan metode penelitian studi kasus. Pengumpulan data dilakukan dengan wawancara dan dokumentasi. Hasil penelitian ini menunjukkan bahwa manajemen mutu dalam pembelajaran bahasa Arab di sekolah ditemukan pada a) pembelajaran bahasa Arab di sekolah menjadi lebih tepat, dengan membangun pembelajaran yang interaktif, inspiratif, menyenangkan dan memotivasi. b) Pembelajaran bahasa Arab di sekolah semakin baik, sehingga mampu memenuhi standar kelulusan siswa, dengan membangun fasilitas penunjang pembelajaran seperti laboratorium bahasa dan lingkungan bahasa. Penelitian ini juga mengungkapkan bahwa ada faktor-faktor yang mendukung keberhasilan pembelajaran bahasa Arab, yaitu faktor internal dan eksternal, seperti lingkungan bahasa, motivasi diri, guru yang profesional dan fasilitas belajar yang memadai. Kata Kunci: Manajemen, Kualitas, Bahasa Arab